2018
DOI: 10.1083/jcb.201701158
|View full text |Cite
|
Sign up to set email alerts
|

Chemical waves in cell and developmental biology

Abstract: Deneke and Di Talia review how the spatiotemporal coordination of cellular functions across large distances is controlled by chemical waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 106 publications
(163 reference statements)
2
92
0
Order By: Relevance
“…To summarize, using in vitro reconstitution and theoretical modeling, we found that the minimal Rab5 regulatory network is ultrasensitive and bistable, likely prerequisites for the decisive signaling reactions controlling vesicle traffic. We have demonstrated that the architecture of the Rab5 activation network supports the formation of spatiotemporal patterns such as activation fronts, as found for other bistable systems with a local positive feedback and global inhibition (46). We also found that Rab5 activation in this minimal network can occur stochastically, and we identified the low amounts of non-active Rab5[GDP] as a potential source for this stochastic behavior.…”
Section: Discussionsupporting
confidence: 67%
“…To summarize, using in vitro reconstitution and theoretical modeling, we found that the minimal Rab5 regulatory network is ultrasensitive and bistable, likely prerequisites for the decisive signaling reactions controlling vesicle traffic. We have demonstrated that the architecture of the Rab5 activation network supports the formation of spatiotemporal patterns such as activation fronts, as found for other bistable systems with a local positive feedback and global inhibition (46). We also found that Rab5 activation in this minimal network can occur stochastically, and we identified the low amounts of non-active Rab5[GDP] as a potential source for this stochastic behavior.…”
Section: Discussionsupporting
confidence: 67%
“…Because the signaling wave always initiates in one-and two-dimensional environments, it can in principle be initiated by a single cell. As random activation of a single cell can initiate a signaling wave that fixes the entire population to maximal activation, these signaling dynamics have typically been thought of as unstable [24]. Yet, even in one-and two-dimensional environments, the initiation time for colonies smaller than D/v can be many orders of magnitude larger than the characteristic time scale of D/v 2 (Fig.…”
Section: Signaling Wave Initiationmentioning
confidence: 99%
“…The densities of the entropy production rates, as well as their global counterparts, are non-negative quantities and they vanish only at equilibrium. Indeed, the reaction entropy production rate can be written as Tσ rct = RT j ρ ln(j +ρ /j −ρ ) ≥ 0, with the aid of the local detailed balance (8) and the mass-action kinetics (2). Similarly, the diffusion entropy production rate can be written as…”
Section: Reaction-diffusion Systemsmentioning
confidence: 99%